A Study on Sustainability of a Multipurpose Cooker by Using SolidWorks Sustainability Analysis - Siraj, Suryana; Mohd Fahrul Hasan (Research Progress in Mechanical and Manufacturing Engineering, 2025)
This study focuses on designing and assessing the sustainability of a multipurpose cooker to meet the growing demand for eco-friendly, energy-efficient kitchen appliances. Using SolidWorks Sustainability tools, the research evaluates material selection, thermal efficiency, and environmental impact through lifecycle analysis. Key metrics such as carbon footprint, energy consumption, air acidification, and water eutrophication are analyzed. The study balances environmental benefits with production costs, comparing design alternatives to identify the optimal solution for performance and sustainability. The findings aim to reduce waste, enhance recyclability, and promote durable, safe, and cost-effective cooker designs, contributing to sustainable engineering practices.